(untitled) (JOURNAL OF LANDSCAPE ECOLOGY | TÁJÖKÖLÓGIAI LAPOK, 2014)
Hungarian red clays are the result of soil formation from previous geologic periods. They were spread over areas which were dry during the Tertiary Period and were not covered by sediments. Varying views on the formation, properties and distribution of red soils in Hungary have been published by numerous authors. Geologists took an early stand on the origin of red clays. According to the literature there are mayor differences in discussing red soils (between red soils and red clays) concerning the conditions of formation and their characteristics. Our red clays are similar to the tropical and sub-tropical ferrolite soils in relation to their formation and mineral characteristics. One of our aims is to explore the similarities in processes and characteristics, which would substantially help in classification. In this paper we report on the results of soil studies carried out on red clays and soils in Hungary. The SiO2/R2O3 molecular ratios of the clay fraction are much lower, but do not all suggest a definite ferrallitous weathering. The ratios often show a value around 2 for the samples. We can assume that the lower these ratios are the stronger the earlier tropical or sub-tropical weathering processes were. Usually kaolinite occurs or is even dominant amongst the clay minerals in the case of soil with lower SiO2/R2O3 ratio, which also suggests intense weathering and transforming processes. On the basis of total chemical analysis, the molecular ratio of these soils is similar to the oldest tropical soils. The type of weathering was ferrallitic. These soils contain a high amount of boehmite and gibbsite, but little ferric oxide.